2022
DOI: 10.1007/s10877-022-00840-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neonatal respiratory rate variability

Abstract: Accurate measurement of respiratory rate (RR) in neonates is challenging due to high neonatal RR variability (RRV). There is growing evidence that RRV measurement could inform and guide neonatal care. We sought to quantify neonatal RRV during a clinical study in which we compared multiparameter continuous physiological monitoring (MCPM) devices. Measurements of capnography-recorded exhaled carbon dioxide across 60-s epochs were collected from neonates admitted to the neonatal unit at Aga Khan University-Nairob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…When measuring RR, if the intent is to measure the underlying physiology that is triggering each breath, measuring a breath interval is likely to be more precise than counting breaths. 4 Given that the RRate app's average number of taps to measure RR in the study was 6, at a median RR of 55, the RRate measured the RR in 6.5 seconds, and would not be equivalent to a RR measured over 30 or 60 seconds, especially in infants in whom RR variability is much higher at faster RRs. 5 To facilitate a more accurate comparison of the two RR apps and a more precise estimate of the repeatability of breath count observations, the authors could consider measuring the breath intervals by identifying a specific video frame in the video recordings used in the study for each breath.…”
Section: Counting: An Imprecise Reference Standard For Respiratory Ra...mentioning
confidence: 97%
“…When measuring RR, if the intent is to measure the underlying physiology that is triggering each breath, measuring a breath interval is likely to be more precise than counting breaths. 4 Given that the RRate app's average number of taps to measure RR in the study was 6, at a median RR of 55, the RRate measured the RR in 6.5 seconds, and would not be equivalent to a RR measured over 30 or 60 seconds, especially in infants in whom RR variability is much higher at faster RRs. 5 To facilitate a more accurate comparison of the two RR apps and a more precise estimate of the repeatability of breath count observations, the authors could consider measuring the breath intervals by identifying a specific video frame in the video recordings used in the study for each breath.…”
Section: Counting: An Imprecise Reference Standard For Respiratory Ra...mentioning
confidence: 97%
“…Respiratory events and associated desaturation events affect cerebral physiology and contain relevant information about cerebral hemodynamics [7][8][9][10]. Hence, continuous monitoring of RR changes in hospitalized neonates and the impact on cerebral hemodynamics is of importance in clinical practice [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is an increment in the number of neonatal admission due to respiratory distress [4]. Detection and assessment of respiratory dysfunction at an early stage enable appropriate medical treatment, and respiratory monitoring saves the lives of newborns [5].…”
Section: Introductionmentioning
confidence: 99%